Hubungan Kontrol Tekanan Darah dan Self-Efficacy dengan Indeks Katz dan Kualitas Hidup Pasien Pasca Stroke - Maulvi Agri Sadewa; Retno Setyawati; Suyanto Suyanto (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Stroke can lead to disability and weakness, resulting in a decline in functional abilities and making patients dependent on others. Independence in performing daily activities is crucial for post-stroke patients as it fosters a sense of purpose and improves their spirit for life, ultimately having a positive impact on their quality of life. Blood pressure control and self-efficacy play significant roles in managing independence and improving the quality of life for post-stroke patients. To determine the relationship between blood pressure control and self-efficacy with the Katz Index and the quality of life in post-stroke patients. This quantitative study employed a correlational design with a cross-sectional approach. Data were collected using questionnaires distributed to 70 respondents. The sampling method used was non-probability sampling with accidental sampling. The data were analyzed using Lambda and Spearman’s rank correlation tests. The findings revealed that most respondents had controlled blood pressure (50 respondents), high self-efficacy (51 respondents), Katz Index category A (52 respondents), and a high quality of life (54 respondents). The study concludes that there is a relationship between blood pressure control and self-efficacy with the Katz Index and the quality of life in post-stroke patients.